Comparative Analysis of Cost and Time Between Flexible and Rigid Pavement on the Siwalanpanji Kemiri - Hariyanto, Tri Perwira; Oetomo, Wateno; Marleno, Risma (Pelopor Publikasi Akademika, 2025)
This research presents a comparative analysis of the cost and construction time between flexible and rigid pavement structures on the Siwalanpanji-Kemiri road section in Sidoarjo Regency, East Java, Indonesia. The area is undergoing a functional shift from rural to industrial, necessitating durable infrastructure to accommodate increasing heavy vehicle traffic. Using the 2024 Indonesian Pavement Design Manual (MDPJ), the research evaluates the technical and economic viability of both pavement types over 20-year and 40-year service lives. Key parameters include Average Daily Traffic (ADT) projections, Cumulative Equivalent Single Axle Load (CESAL), and subgrade strength derived from Dynamic Cone Penetrometer (DCP) tests. These inputs inform pavement thickness designs and cost estimates based on local unit prices (HSPK). Findings reveal that flexible pavement offers faster construction (9 days vs. 39–49 days for rigid) but incurs 38% higher long-term costs due to frequent maintenance. Rigid pavement, despite longer initial construction time, proves more economical over 40 years, with lower maintenance needs and superior durability under heavy loads. Cost analysis shows rigid pavement saves up to IDR 3.5 billion compared to flexible alternatives over four decades. The study also highlights the sustainability benefits of reusing existing materials, aligning with environmental goals. These results provide actionable insights for the Sidoarjo Public Works Agency, emphasizing rigid pavement as the optimal choice for industrializing corridors. The research underscores the importance of life-cycle cost analysis and context-specific design in infrastructure planning, offering a model for similar regions facing rapid urbanization and traffic growth.